Lithium secondary battery having high energy density

By using sulfur-carbon composite materials and specific compounds in lithium-sulfur batteries, the problems of large amount of electrolyte and reduced positive electrode efficiency are solved, and a high-energy density lithium-sulfur battery is realized, with an energy density of more than 430 Wh/kg.

CN119487662APending Publication Date: 2025-02-18LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380048167.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-09
Filing Date
2023-11-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In order to achieve high energy density, existing lithium-sulfur batteries have problems such as large electrolyte volume, reduced positive electrode efficiency and deterioration of negative electrode, resulting in the inability to fully improve the energy density.

Method used

The electrolytic mass and improve the efficiency of the positive electrode by using a positive electrode and an anode containing a sulfur-carbon composite material in a lithium sulfur battery and a compound containing a specific X-ray diffraction pattern at a discharge depth of 15% to 80%.

Benefits of technology

The high energy density of lithium-sulfur batteries is achieved, which is specifically manifested as the energy density reaches more than 300 Wh/kg and further increases to more than 430 Wh/kg.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487662A_ABST
    Figure CN119487662A_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium-sulfur battery having a high energy density, and provides a lithium-sulfur battery comprising a compound defined by a characteristic peak in an X-ray diffraction (XRD) pattern in a discharged state. The lithium-sulfur battery according to one aspect of the present invention has a high energy density. In particular, the lithium-sulfur battery according to the present invention can have an energy density of 300 Wh / kg or more, further 430 Wh / kg or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium secondary battery, and more particularly to a lithium-sulfur battery with high energy density.

[0002] This application claims priority to Korean Patent Application No. 10-2023-0074500 filed on June 9, 2023, and Korean Patent Application No. 10-2023-0155551 filed on November 10, 2023, in Korea, the disclosures of which are incorporated herein by reference. Background Art

[0003] As the application of lithium secondary batteries expands from portable electronic devices to electric vehicles (EVs) and power storage systems (ESSs), there is an increasing demand for lithium secondary batteries with high capacity, high energy density, and long life.

[0004] Among lithium secondary batteries, lithium-sulfur batteries are battery systems that use a sulfur-based material containing a sulfur-sulfur bond as a positive electrode active material, and lithium metal, a carbon-based material in which lithium ions are intercalated / deintercalated, or silicon or tin that forms an alloy with lithium as a negative electrode active material.

[0005] In lithium-sulfur batteries, sulfur, the main material of the positive electrode active material, has a low atomic weight, is abundant, easily available, inexpensive, non-toxic and environmentally friendly.

[0006] In addition, when lithium metal is used in the negative electrode, the lithium-sulfur battery theoretically shows the conversion reaction of lithium ions and sulfur at the positive electrode (S8+16Li + +16e - →8Li2S) has a specific capacity of 1,675 mAh / g and an energy density of 2,600 Wh / kg. Since the theoretical energy density of lithium-sulfur batteries is much higher than that of other battery systems currently under research (Ni-MH battery: 450 Wh / kg, Li-FeS battery: 480 Wh / kg, Li-MnO2 battery: 1,000 Wh / kg, Na-S battery: 800 Wh / kg, lithium-ion battery: 250 Wh / kg), high-capacity, environmentally friendly and low-cost lithium secondary batteries have attracted attention among the secondary batteries that have been developed and are being developed.

[0007] However, the large amount of electrolyte, reduced cathode efficiency, and degradation of the anode prevent the full realization of theoretical capacity, thereby failing to fully increase energy density.

[0008] Under such circumstances, research has been conducted to realize lithium secondary batteries having high energy density. Summary of the invention

[0009] Technical issues

[0010] The present invention aims to solve the above problems, and thus the present invention aims to provide a lithium-sulfur battery with high energy density.

[0011] In particular, the present invention aims to provide a lithium-sulfur battery which reduces the amount of electrolyte and improves the efficiency of a positive electrode to increase capacity, thereby achieving high energy density.

[0012] Technical Solution

[0013] In order to solve the above problems, according to one aspect of the present invention, a lithium-sulfur battery according to the following exemplary embodiment is provided.

[0014] A lithium-sulfur battery according to a first exemplary embodiment includes:

[0015] A positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte comprising a sulfur-carbon composite material,

[0016] The lithium-sulfur battery comprises a compound having three or more characteristic peaks selected from the following diffraction angles (2θ values) of an X-ray diffraction (XRD) pattern at a depth of discharge (DOD) of 15% to DOD 80%: 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2° and 15.0±0.2°.

[0017] According to the second exemplary embodiment, DOD 15% to DOD 80% may be a state having a potential of 1.7 V to 2.2 V in the first exemplary embodiment.

[0018] According to the third exemplary embodiment, in the first or second exemplary embodiment, DOD 15% to DOD 80% may be a state having a discharge capacity per sulfur (S) weight of 150 to 960 mAh / g(s).

[0019] According to a fourth exemplary embodiment, in any one of the first to third exemplary embodiments, the compound may have four or more characteristic peaks selected from the diffraction angles.

[0020] According to a fifth exemplary embodiment, in any one of the first to fourth exemplary embodiments, the compound may include a diffraction angle (2θ value) of an XRD pattern of 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2°, and 15.0±0.2°.

[0021] According to the sixth exemplary embodiment, in any one of the first to fifth exemplary embodiments, the sulfur-carbon composite material may have a sulfur / carbon (S / C) weight ratio of 2.3 g / g or more.

[0022] According to the seventh exemplary embodiment, in any one of the first to sixth exemplary embodiments, the positive electrode may include: a current collector; and a positive electrode active material layer comprising a sulfur-carbon composite material on at least one surface of the current collector, and the weight of the sulfur-carbon composite material is 90 weight % or more based on the total weight of the positive electrode active material layer.

[0023] According to the eighth exemplary embodiment, in any one of the first to seventh exemplary embodiments, the positive electrode may have a capacity of 2 to 5 mAh / cm 2 of sulfur (S) loading.

[0024] According to a ninth exemplary embodiment, in any one of the first to eighth exemplary embodiments, the negative electrode may have a thickness of 40 to 80 μm.

[0025] According to the tenth exemplary embodiment, in any one of the first to ninth exemplary embodiments, a weight ratio of the electrolyte to elemental sulfur (S) in the sulfur-carbon composite material (E1 / S weight ratio) may be 2.5 g / g or less.

[0026] According to the eleventh exemplary embodiment, in any one of the first to tenth exemplary embodiments, the lithium-sulfur battery may have a capacity of 1.4 mAh / cm 2 The above S X , S X Satisfies the following formula 1:

[0027] [Formula 1]

[0028] S X =S PE / S EL / S

[0029] Among them, S PE is the sulfur (S) loading in the cathode, and

[0030] Among them, SEL / S It is the weight ratio of the electrolyte to the elemental sulfur (S) in the sulfur-carbon composite material (El / S weight ratio).

[0031] According to the twelfth exemplary embodiment, in any one of the first to eleventh exemplary embodiments, the energy density of the lithium-sulfur battery may be 430 Wh / kg or more.

[0032] According to a thirteenth exemplary embodiment, in any one of the first to twelfth exemplary embodiments, the lithium-sulfur battery may be a pouch-type battery or a cylindrical battery.

[0033] According to another aspect of the present invention, an evaluation method according to the following exemplary embodiment is provided.

[0034] The evaluation method according to the fourteenth exemplary embodiment is a method of evaluating the energy density of a lithium-sulfur battery, the lithium-sulfur battery comprising: a positive electrode including a sulfur-carbon composite material, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, the method comprising:

[0035] A lithium-sulfur battery containing a compound having three or more characteristic peaks selected from the following diffraction angles (2θ values) of an XRD pattern at DOD 15% to DOD 80% is determined to be a battery with a high energy density.

[0036] According to the fifteenth exemplary embodiment, the battery having high energy density in the fourteenth exemplary embodiment may be a battery having an energy density of 430 Wh / kg or more.

[0037] Beneficial Effects

[0038] A lithium-sulfur battery according to one aspect of the present invention has a high energy density.

[0039] In particular, the lithium-sulfur battery of the present invention may have an energy density of 300 Wh / kg or more, and further, 430 Wh / kg or more. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a graph showing the discharge capacity evaluation results of Example 1, Comparative Example 2 and Comparative Example 3 in the present invention.

[0041] Figure 2aThe real-time charge / discharge X-ray diffraction (XRD) measurement results of the lithium-sulfur battery of Example 1 in the present invention are shown.

[0042] Figure 2b Shown in Figure 2a XRD pattern at depth of discharge (DOD) 22% in the real-time charge / discharge XRD pattern obtained in .

[0043] Figure 3a The real-time charge / discharge XRD measurement results of the lithium-sulfur battery of Comparative Example 1 in the present invention are shown.

[0044] Figure 3b Shown in Figure 3a XRD pattern at DOD 22% in the real-time charge / discharge XRD pattern obtained in .

[0045] Figure 4a The real-time charge / discharge XRD measurement results of the lithium-sulfur battery of Comparative Example 2 in the present invention are shown.

[0046] Figure 4b Shown in Figure 4a XRD pattern at DOD 22% in the real-time charge / discharge XRD pattern obtained in .

[0047] Figure 5a The real-time charge / discharge XRD measurement results of the lithium-sulfur battery of Comparative Example 3 in the present invention are shown.

[0048] Figure 5b Shown in Figure 5a XRD pattern at DOD 22% in the real-time charge / discharge XRD pattern obtained in . DETAILED DESCRIPTION

[0049] Hereinafter, the present invention is described in more detail.

[0050] Unless the context clearly indicates otherwise, the terms “comprising”, “including” or “having” when used in the present invention specify the presence of stated elements, but do not preclude the presence or addition of one or more other elements.

[0051] Additionally, the terms "about" and "substantially" as used herein are used in the sense of the value or close thereto when given the manufacturing and material tolerances inherent in the circumstances, and are used to prevent unscrupulous infringers from improperly taking advantage of the exact or absolute values ​​set forth in the present invention to aid in the understanding of the present invention.

[0052] Throughout the present invention, "A and / or B" means A or B or both.

[0053] Throughout the present invention, unless otherwise specified, temperatures are expressed in degrees Celsius, with the unit being °C.

[0054] As used herein, the term "composite material" refers to a combination of two or more materials having physically and chemically different phases and exhibiting more effective functions.

[0055] As used herein, the term "(poly)sulfide" encompasses the concepts of "(poly)sulfide ion (S x 2- , 1 ≤ x ≤ 8)" and "(poly)lithium sulfide (Li2S x or Li2S x - , 1 ≤ x ≤ 8)".

[0056] As used herein, the term "polysulfide" encompasses the concepts of "polysulfide ion (S x 2- , 1 < x ≤ 8)" and "polylithium sulfide (Li2S x or Li2S x - , 1 < x ≤ 8)".

[0057] Unless the context clearly indicates otherwise, the unit "mAh / g s " refers to the capacity per unit weight of sulfur (S), and can be used interchangeably with mAh / g(s), mAh / gs, or any other form of unit expression.

[0058] Unless the context clearly indicates otherwise, as used herein, the unit "mg s / cm 2 " refers to the weight of sulfur (S) per unit area, and can be used interchangeably with mg(s) / cm 2 or mAh / cm 2 or any other form of unit expression of the loading amount.

[0059] According to one aspect of the present invention, a lithium-sulfur battery having a high energy density is provided.

[0060] The lithium-sulfur battery according to one aspect of the present invention includes: a positive electrode containing a sulfur-carbon composite material, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.

[0061] In an exemplary embodiment of the present invention, the lithium-sulfur battery may include: a case accommodating an electrode assembly including a positive electrode, a negative electrode, and a separator, and an electrolyte.

[0062] The lithium-sulfur battery contains a compound which, in its discharged state, particularly at a depth of discharge (DOD) of 15% to 80%, has more than three characteristic peaks among the diffraction angles (2θ values) of an X-ray diffraction (XRD) pattern selected from the following: 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2°, and 15.0±0.2°.

[0063] In an exemplary embodiment of the present invention, the lithium-sulfur battery may contain a compound which, in its discharged state, has more than three characteristic peaks among the diffraction angles (2θ values) of an XRD pattern selected from 7.1°, 9.0°, 9.4°, 9.6°, 9.9°, 10.0°, 10.4°, 11.0°, 11.6°, 12.1°, 13.3°, 14.5°, and 15.0°.

[0064] In an exemplary embodiment of the present invention, the lithium-sulfur battery may specifically contain a compound which, at a DOD of 15% to 80%, has more than three characteristic peaks among the diffraction angles (2θ values) of an XRD pattern selected from 7.1°, 9.0°, 9.4°, 9.6°, 9.9°, 10.0°, 10.4°, 11.0°, 11.6°, 12.1°, 13.3°, 14.5°, and 15.0°.

[0065] The lithium-sulfur battery according to one aspect of the present invention contains a compound which, in its discharged state, has the above XRD pattern.

[0066] The lithium-sulfur battery contains inorganic sulfur (S8) as a positive electrode active material. In the lithium-sulfur battery, polysulfide lithium is formed by a reduction reaction at the positive electrode during discharge. The compound may be a crystalline form of polysulfide lithium formed by the reduction reaction of inorganic sulfur (S8). Since the lithium-sulfur battery according to one aspect of the present invention contains a crystalline form of polysulfide lithium which, in its discharged state, has the above XRD pattern, a high energy density can be achieved.

[0067] In an exemplary embodiment of the present invention, the compound may be a crystalline form of polysulfide lithium, and herein, the polysulfide lithium may be Li2S x and Li2S x - (1 < x ≤ 8) of at least one.

[0068] In the present invention, the compound can be defined as a crystalline form of lithium polysulfide having three or more characteristic peaks selected from diffraction angles (2θ values) of 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2° and 15.0±0.2°.

[0069] In an exemplary embodiment of the present invention, the compound may be a crystalline form of lithium polysulfide formed under high energy density conditions during discharge of a lithium-sulfur battery having high energy density. For example, a lithium-sulfur battery having high energy density may have a low El / S (electrolyte / sulfur) ratio as described below, and when lithium polysulfide formed during operation of the lithium-sulfur battery is dissolved in a small amount of electrolyte at a high concentration, a crystalline form showing a characteristic peak of a diffraction angle of an XRD pattern may be formed, but the formation mechanism of the compound is not limited thereto.

[0070] In an exemplary embodiment of the present invention, the compound may have four or more, for example, five or more characteristic peaks selected from the above diffraction angles (2θ values). Specifically, the compound may have 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13 characteristic peaks.

[0071] In an exemplary embodiment of the present invention, the compound may include a diffraction angle (2θ value) of the XRD pattern of 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2°, and 15.0±0.2°.

[0072] In an exemplary embodiment of the present invention, the compound may include diffraction angles (2θ values) of the XRD pattern of 7.1°, 9.0°, 9.4°, 9.6°, 9.9°, 10.0°, 10.4°, 11.0°, 11.6°, 12.1°, 13.3°, 14.5°, and 15.0°.

[0073] In an exemplary embodiment of the present invention, the compound may be contained on at least one of the positive electrode, the negative electrode, the separator, the electrolyte, and the inner surface of the shell of the lithium-sulfur battery, and the XRD pattern may be obtained by non-destructive analysis of the lithium-sulfur battery. That is, the XRD pattern may be measured without disassembling the lithium-sulfur battery.

[0074] In an exemplary embodiment of the present invention, an XRD pattern may be obtained from a lithium-sulfur battery. Specifically, the XRD pattern may be obtained by nondestructive analysis of the lithium-sulfur battery. For example, the XRD pattern may be obtained by Operando X-ray diffraction (Operando XRD) analysis.

[0075] More specifically, the Mo Kα X-ray (λ=0.709 ) XRD patterns are obtained by measuring 2θ (2θ) values ​​in a range between 7° and 17° in transmission mode. Thus, XRD patterns can be measured using an X-ray wavelength of 0.709 Å by XRD. In this case, each pattern can be obtained at intervals of 0.014°, for a total of 3 minutes. Wherein, the error range of 2θ measured by XRD can be ± 0.2°, more specifically ± 0.1°.

[0076] According to one aspect of the present invention, since the compound having the XRD pattern is contained in the lithium-sulfur battery in the discharged state, the XRD measurement and the charging / discharging of the lithium-sulfur battery can be performed simultaneously. Specifically, the XRD measurement can be continuously performed while the lithium-sulfur battery is charged / discharged.

[0077] More specifically, an XRD pattern may be obtained from real-time charge / discharge XRD measurement results using Operando X-ray diffraction.

[0078] In an exemplary embodiment of the present invention, when the lithium-sulfur battery is a pouch-type battery (bag-shaped battery), a pressing jig equipped with a Be window may be used for XRD measurement during operation of the lithium-sulfur battery, but the present invention is not limited thereto.

[0079] As described above, the XRD pattern of the compound may be obtained in a discharged state of a lithium-sulfur battery, and in this case, the XRD pattern is obtained at DOD 15% to DOD 80%.

[0080] In the present invention, DOD 15% to DOD 80% refers to a state in which the lithium-sulfur battery is discharged by 15% to 80% from a fully charged state, ie, a state of charge (SOC) of 100%.

[0081] In an exemplary embodiment of the present invention, in order to easily detect the characteristic peak of the compound, the XRD peak can be detected at any discharge state of the lithium-sulfur battery, and for example, the XRD peak can be detected at DOD 20% to DOD 60% or DOD 20% to DOD 50%. For example, the XRD peak of the compound can be detected based on DOD 22% of the lithium-sulfur battery, but the present invention is not limited to a specific discharge state.

[0082] In an exemplary embodiment of the present invention, DOD 15% may be a state having a potential of 2.2 V or less, and DOD 15% to DOD 80% may be a state having a potential of 1.7 V to 2.2 V, for example, but the present invention is not limited thereto.

[0083] In an exemplary embodiment of the present invention, the total discharge capacity of the lithium-sulfur battery may be 1,000 mAh / g ( S ) or more. For example, based on the discharge capacity per unit sulfur (S) weight, the total discharge capacity of the lithium-sulfur battery can be 1,000 to 1,300 mAh / g ( S ), specifically 1,100 to 1,200 mAh / g ( S ), for example 1,180mAh / g( S ). DOD 15% may be a state in which the capacity is 15% of the total discharge capacity, and DOD 80% may be a state in which the capacity is 80% of the total discharge capacity. For example, DOD 15% to DOD 80% may be a discharge capacity based on a unit weight of sulfur (S) with a capacity of 150 to 960 mAh / g ( S )'s capacity status.

[0084] As described above, a lithium-sulfur battery including a compound having a characteristic peak in an XRD pattern at DOD 15% to DOD 80% may have a high energy density.

[0085] In an exemplary embodiment of the present invention, the lithium-sulfur battery may satisfy S according to the following formula 1: X The value is 1.4 mAh / cm 2 above:

[0086] [Formula 1]

[0087] S X =S PE / S EL / S

[0088] Among them, S PE represents the sulfur (S) loading in the cathode, and

[0089] S EL / S It represents the weight ratio of the electrolyte to the elemental sulfur (S) in the sulfur-carbon composite material (El / S weight ratio).

[0090] Specifically, S PE The unit can be mAh / cm 2 The value of .

[0091] In addition, S EL / SIt is a dimensionless value in the same manner as the weight ratio (E1 / S) of the electrolyte to the elemental sulfur (S) in the sulfur-carbon composite material described below.

[0092] In an exemplary embodiment of the present invention, according to the above formula 1, S X The value may be 1.4 mAh / cm² or more, for example, in a range between 1.4 mAh / cm² and 10 mAh / cm², specifically in a range between 1.5 mAh / cm² and 6 mAh / cm², more specifically in a range between 1.6 mAh / cm² and 4 mAh / cm², for example, in a range between 1.7 mAh / cm² and 2.5 mAh / cm². In an exemplary embodiment of the present invention, when the value according to the above formula 1 satisfies the above range, the lithium-sulfur battery may include a compound having the above XRD peak, and thus may show high energy density, but the present invention is not limited thereto.

[0093] Hereinafter, each component of the lithium-sulfur battery will be described in detail.

[0094] positive electrode

[0095] In an exemplary embodiment of the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer on one side or both sides of the positive electrode current collector.

[0096] The positive electrode current collector is not limited to a specific type, and may include any positive electrode current collector that supports the positive electrode active material and has high conductivity without causing any chemical changes in the battery. For example, the positive electrode current collector may include: copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon; copper or stainless steel surface-treated with carbon, nickel, silver, etc.; aluminum-cadmium alloy, etc.

[0097] The positive electrode current collector may have a finely concavoconvex surface to increase the bonding strength with the positive electrode active material. Various forms such as films, sheets, foils, screens, nets, porous bodies, foams, nonwoven fabrics, etc. may be used.

[0098] The positive electrode active material layer contains a positive electrode active material, and may further contain a conductive material, a binder, an additive, and the like.

[0099] In an exemplary embodiment of the present invention, the positive electrode active material includes a sulfur-carbon composite material.

[0100] In an exemplary embodiment of the present invention, the sulfur-carbon composite material may include: a porous carbon material; and a sulfur compound supported on at least one of the pores of the porous carbon material and the surface of the porous carbon material. Sulfur used as a positive electrode active material does not have conductivity and can be used in combination with a conductive material such as a carbon material, and in order to support sulfur, a porous carbon material can be used. In addition, a sulfur compound is added as a positive electrode active material, and may include, for example, inorganic sulfur (S8), lithium sulfide (Li2S), (poly) lithium sulfide (Li2S x , 1≤x≤8 (integer)), disulfide compounds, carbon-sulfur polymers ((C2S y ) n , y=2.5 to 50, n≥2) or two or more thereof. Preferably, the sulfur compound may be inorganic sulfur (S8).

[0101] In an exemplary embodiment of the present invention, the porous carbon material is not limited to a specific type and may include any porous carbon material that supports a sulfur compound as a positive electrode active material, provides a skeleton for uniformly and stably fixing the sulfur compound, and improves positive electrode conductivity.

[0102] Porous carbon materials can generally be prepared by carbonizing precursors of various carbon materials. Porous carbon materials contain irregular pores therein. The average diameter of the pores may be in the range of 1 to 200 nm, and the porosity may be in the range of 10 to 90% by volume of the total volume of the porous carbon material. When the average diameter of the pores is less than the above range, it is impossible to impregnate sulfur because the pore size is only at the molecular level. On the contrary, when the average diameter exceeds the above range, the porous carbon material is not suitable for use in the electrode manufacturing process because of its low mechanical strength.

[0103] In an exemplary embodiment of the present invention, the "average diameter of the pores" can be measured by a method for measuring the pore size of a porous material known in the art, and the measuring method is not limited to a specific method. For example, the pore size can be measured by a scanning electron microscope (SEM), a field emission electron microscope, a laser diffraction or a Brunauer-Emmett-Teller (BET) method. For example, a commercially available laser diffraction particle size analyzer (e.g., Microtrac MT3000) can be used to perform measurements using laser diffraction. In addition, the measurement by BET can be performed, for example, using a BELSORP series analyzer (BEL Japan), but is not limited thereto.

[0104] In an exemplary embodiment of the present invention, "porosity" refers to the ratio of the volume occupied by pores to the total volume of the structure in %, and can be used interchangeably with the terms pore ratio, void ratio, etc. In the present invention, there is no particular limitation on the method for measuring porosity. According to an exemplary embodiment of the present invention, porosity can be measured by a BET method using nitrogen, a mercury (Hg) porosimeter, or ASTM D2873.

[0105] The porous carbon material may be in the shape of a sphere, a rod, a needle, a plate, a tube, or a block and is not limited to a specific shape, and any shape commonly used in lithium-sulfur batteries may be used.

[0106] The porous carbon material may include any commonly used porous carbon material having a porous structure and a large specific surface area. For example, the porous carbon material may be at least one selected from the following: graphite; graphene; carbon black such as Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon nanotubes (CNT) such as single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), etc.; carbon fibers such as graphite nanofibers (GNF), carbon nanofibers (CNF), activated carbon fibers (ACF), etc.; graphite such as natural graphite, artificial graphite, expanded graphite, etc.; and activated carbon, but not limited thereto. Preferably, the porous carbon material may be a carbon nanotube.

[0107] In an exemplary embodiment of the present invention, the porous carbon material may include, for example, carbon nanotubes (CNTs).

[0108] In an exemplary embodiment of the present invention, the sulfur-carbon composite material may have, for example, a sulfur / carbon (S / C) weight ratio of 2.3 g / g or more. For example, the sulfur-carbon composite material may have an S / C weight ratio of 2.3 g / g. When the S / C ratio of the sulfur-carbon composite material is within the above range, it may be preferred in terms of the electron transfer ability (conductivity) and electrochemical specific surface area of ​​the sulfur-carbon composite material, and, for example, the available surface area of ​​the sulfur-carbon composite material is increased, thereby inhibiting the dissolution of sulfur from the positive electrode, but the present invention is not limited thereto.

[0109] In an exemplary embodiment of the present invention, the S / C ratio can be calculated by the weight (g) of sulfur and the weight (g) of carbon present in the sulfur-carbon composite material. Alternatively, the S / C ratio can be calculated by the weight (wt%) of sulfur and the weight (wt%) of carbon based on the total weight of the sulfur-carbon composite material. Therefore, the S / C ratio can be dimensionless.

[0110] In an exemplary embodiment of the present invention, the S / C weight ratio may be, for example, in the range of 0.5 to 5.0, 0.5 to 4.0, 1.0 to 3.0, 1.5 to 2.5, 2.0 to 2.45, 2.25 to 2.35, or 2.3 to 3. For example, the S / C ratio may be calculated by the weight of inorganic sulfur (S8) / the weight of the porous conductive material. For example, the S / C ratio may be calculated by the S8 / CNT weight ratio.

[0111] The sulfur-carbon composite material can be prepared by any method commonly used in the art without limitation. For example, the composite material can be prepared by simply mixing sulfur and a porous carbon material and then heat treating the mixture.

[0112] In addition to the above composition, the positive electrode active material may further include at least one selected from the group consisting of transition metal elements, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0113] Transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au or Hg, Group IIIA elements may include Al, Ga, In, Tl, etc., and Group IVA elements may include Ge, Sn, Pb, etc.

[0114] In an exemplary embodiment of the present invention, the content of the sulfur-carbon composite material may be 50% by weight or more based on the total weight of the positive electrode. Specifically, based on the total weight of the positive electrode active material layer, the content of the sulfur-carbon composite material may be, for example, 80% by weight or more, 90% by weight or more, or 95% by weight or more. Specifically, based on the total weight of the positive electrode active material layer, the content of the sulfur-carbon composite material may be 80% by weight to 100% by weight, more specifically 85% by weight to 99% by weight, 90% by weight to 99% by weight, 95% by weight to 98% by weight, 95% by weight to 97% by weight, or 96% by weight. When the amount of the sulfur-carbon composite material is lower than the above range, the relative amount of auxiliary materials such as conductive materials and adhesives is high, and the amount of the sulfur-carbon composite material is low, which makes it difficult to achieve a battery with high capacity and high energy density. On the contrary, when the amount of the sulfur-carbon composite material exceeds the above range, the relative amount of the conductive material or adhesive as described below is low and the physical properties of the electrode are reduced.

[0115] The conductive material serves as a path for moving electrons from the current collector to the positive active material by electrically connecting the electrolyte and the positive active material, and may include but is not limited to any material having conductive properties as a component of the electrode that is physically distinct from the carbon contained in the sulfur-carbon composite material.

[0116] In an exemplary embodiment of the present invention, the conductive material may include, for example: carbon black materials such as Super-P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon black, etc.; carbon derivatives such as carbon nanotubes, fullerenes, etc.; conductive fibers such as carbon fibers, metal fibers, etc.; fluorocarbons; metal powders such as aluminum and nickel powders; conductive polymers such as polyaniline, polythiophene, polyacetylene, polypyrrole, etc.; or mixtures thereof.

[0117] In an exemplary embodiment of the present invention, based on the total weight of the positive electrode active material layer, the content of the conductive material may be 0 to 40% by weight, such as 1 to 40% by weight, 15 to 40% by weight, 20 to 40% by weight, or 25 to 35% by weight, or 0 to 10% by weight, such as 1 to 10% by weight. When the amount of the conductive material is less than the above range, the electron transfer between the positive electrode active material and the current collector is reduced, resulting in lower voltage and capacity. On the contrary, when the amount of the conductive material exceeds the above range, the relative proportion of the positive electrode active material is low, and the total energy (charge) of the battery may be reduced. Therefore, it is preferred to determine the optimal amount within the above range.

[0118] In an exemplary embodiment of the present invention, the binder holds the positive electrode active material on the positive electrode current collector and interconnects the positive electrode active materials to be firmly held together, and may include any binder known in the art.

[0119] For example, the adhesive may include any one selected from the following: a fluororesin adhesive, including polyvinylidene fluoride (PVDF), a polyvinylidene fluoride polymer containing at least one vinylidene fluoride as a repeating unit, polytetrafluoroethylene (PTFE) or a mixture thereof; a rubber adhesive, including styrene-butadiene rubber (SBR), nitrile rubber and styrene-isoprene rubber; an acrylic adhesive; a cellulose adhesive, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose; a polyol adhesive; a polyolefin adhesive, including polyethylene and polypropylene; a polyimide adhesive; a polyester adhesive; a silane adhesive; a polyacrylic acid adhesive; a polyacrylonitrile adhesive; and a mixture or copolymer thereof.

[0120] In an exemplary embodiment of the present invention, the content of the binder may be 1 to 10 weight % based on the total weight of the positive electrode active material layer. When the amount of the binder is less than the above range, the physical properties of the positive electrode may be reduced, and the positive electrode active material and the conductive material may be separated from each other. When the amount of the binder exceeds the above range, the relative proportion of the positive electrode active material and the conductive material in the positive electrode is low, resulting in a low battery capacity. Therefore, it is desirable to determine the optimal amount within the above range.

[0121] In the present invention, the method of manufacturing the positive electrode for a lithium secondary battery is not limited to a specific method, and may include any method known to those skilled in the art or a variation thereof.

[0122] For example, the positive electrode for a lithium secondary battery may be manufactured by preparing a positive electrode slurry composition including the above composition and coating the positive electrode slurry composition on at least one surface of a positive electrode collector to form a positive electrode active material layer.

[0123] The positive electrode slurry composition includes the positive electrode active material described above, and may further include a binder, a conductive material, and a solvent.

[0124] The solvent comprises any solvent that promotes uniform dispersion of the positive electrode active material. The solvent may comprise an aqueous solvent, most preferably water, and in this case, the water may be distilled water or deionized water. However, the present invention is not necessarily limited thereto, and, if necessary, a lower alcohol that is easily mixed with water may be used. The lower alcohol may include methanol, ethanol, propanol, isopropanol and butanol, and preferably, a mixture of a lower alcohol and water may be used.

[0125] The content of the solvent may be such that the concentration is suitable for easy coating, and the specific amount may vary depending on the coating method and equipment.

[0126] If necessary, the positive electrode slurry composition may further include materials commonly used in the technical field to improve functions. For example, such materials may include viscosity modifiers, flow aids, fillers, and the like.

[0127] The method for coating the positive electrode slurry composition is not particularly limited in the present invention, and may include doctor blade, die casting, comma coating, screen printing, etc. In addition, after forming the positive electrode slurry on the substrate, the positive electrode slurry may be coated on the positive electrode collector by pressing or laminating.

[0128] After coating, a drying process may be performed to remove the solvent. The drying process may be performed at a suitable temperature and time to remove the solvent, and the conditions may vary depending on the solvent and are not particularly limited in the present invention. For example, the drying method may include: drying with warm air, hot air or low humidity air; vacuum drying; drying by (far) infrared radiation or electron beam radiation, etc. The drying speed is usually adjusted to remove the solvent as quickly as possible within a speed range at which cracking does not occur in the positive active material layer or the positive active material layer does not peel off from the positive current collector due to stress concentration.

[0129] In addition, the density of the positive electrode active material in the positive electrode can be increased by pressing the current collector after drying. The pressing method may include molding, rolling, and the like.

[0130] The porosity of the positive electrode (specifically the positive electrode active material layer) manufactured by the above composition and manufacturing method can be 50 to 80 volume %, specifically 60 to 75 volume %. When the porosity of the positive electrode is less than 50 volume %, the filling level of the positive electrode slurry composition comprising the positive electrode active material, the conductive material and the binder is too high, so that it is impossible to maintain enough electrolyte to show ionic conduction and / or electrical conduction between the positive electrode active materials. As a result, the output characteristics or cycle characteristics of the battery may deteriorate, and the battery may experience a serious overvoltage and a reduction in discharge capacity. On the contrary, when the positive electrode porosity is too high and exceeds 80 volume %, it may cause poor physical and electrical connection with the current collector, low adhesion strength and little reaction, and filling the electrolyte at high porosity may reduce the energy density of the battery. Therefore, the porosity is appropriately adjusted within the above range.

[0131] In an exemplary embodiment of the present invention, the positive electrode may have a capacity of 2 to 5 mAh / cm 2 For example, the sulfur (S) loading of the positive electrode can be 2.5 to 5 mAh / cm 2 , 3 to 4 mAh / cm 2 , 3.5 to 4 mAh / cm 2 , 3.5 to 5 mAh / cm 2 , 3.6 to 5 mAh / cm 2 , 3.7 to 4.5 mAh / cm 2 , more specifically 3.7 to 4.0 mAh / cm 2 When the sulfur loading amount of the positive electrode is within the above range, it may be advantageous to provide a lithium-sulfur battery with high energy density, but the present invention is not limited thereto.

[0132] The sulfur loading amount can be calculated by measuring the total weight of sulfur (S) contained in the positive electrode as a positive electrode active material and thereby calculating the capacity value of the electrode.

[0133] In an exemplary embodiment of the present invention, the weight of sulfur in the positive electrode may be measured from the positive electrode active material added in the manufacturing step.

[0134] In another exemplary embodiment of the present invention, the weight of sulfur in the positive electrode can be measured by performing thermogravimetric analysis (TGA) on the positive electrode after the positive electrode is manufactured. Specifically, the positive electrode can be obtained by disassembling a lithium-sulfur battery in a charged state under an inactive atmosphere, the positive electrode can be washed with an appropriate solvent and dried, and the amount of sulfur (S) derived from the active material can be measured by TGA of the resultant obtained by peeling off the positive electrode active material layer, but the measuring method is not limited thereto.

[0135] negative electrode

[0136] The negative electrode may include a negative electrode current collector, and a negative electrode active material layer on one or both sides of the negative electrode current collector. Alternatively, the negative electrode may be a lithium metal plate.

[0137] The negative electrode current collector is configured to support the negative electrode active material layer as described in the positive electrode current collector.

[0138] The negative electrode active material layer may contain the negative electrode active material, and may further contain a conductive material, a binder, etc. The conductive material and the binder are as described above.

[0139] The negative electrode active material may include: a reversible intercalation or deintercalation of lithium ions (Li + ) material; a material that reacts with lithium ions to reversibly form a lithium-containing compound; lithium metal; or a lithium alloy.

[0140] Reversibly insert or de-insert lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0141] Preferably, the negative electrode active material may be lithium metal, specifically in the form of a lithium metal film or lithium metal powder.

[0142] In an exemplary embodiment of the present invention, the thickness of the negative electrode may be 40 to 80 μm. For example, the thickness of the negative electrode may be 50 to 70 μm or 60 μm. The thickness of the negative electrode may be measured by any known method for measuring the thickness of each component of a battery, and for example, may be measured using a thickness gauge of Mitutoyo, but is not limited thereto. For example, the thickness of the negative electrode may be measured according to ASTM D374.

[0143] Diaphragm

[0144] The separator separates or insulates the positive electrode and the negative electrode from each other and enables lithium ions to move between the positive electrode and the negative electrode. The separator may be made of a porous non-conductive or insulating material and is not limited to a specific type and may include any separator commonly used in lithium secondary batteries. The separator may be an independent member such as a membrane and may also be a coating added to the positive electrode and / or the negative electrode.

[0145] The separator may preferably have low resistance to the movement of electrolyte ions and high ability to absorb electrolyte.

[0146] In an exemplary embodiment of the present invention, the separator may include a porous substrate. The porous substrate may be any porous substrate commonly used in secondary batteries, and the porous polymer film may be used alone or in a laminated manner. For example, a non-woven fabric or a polyolefin porous film made of high melting point glass fiber, polyethylene terephthalate fiber, etc. may be used, but is not limited thereto.

[0147] In the present invention, the porous substrate is not limited to a specific material, and any porous substrate commonly used in electrochemical devices can be used. For example, the porous substrate may include at least one material selected from the following: polyolefins such as polyethylene, polypropylene, etc.; polyesters such as polyethylene terephthalate, polybutylene terephthalate, etc.; polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthoates, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzodione), ... azoles) and polyacrylates.

[0148] In an exemplary embodiment of the present invention, the thickness of the porous substrate may be 1 to 100 μm, preferably 5 to 50 μm, but is not limited thereto. Although the thickness of the porous substrate is not limited to the above range, when the thickness is too small and below the above lower limit, when the battery is used, the mechanical properties may be reduced and the separator may be easily damaged.

[0149] In an exemplary embodiment of the present invention, the porous substrate may have an average pore diameter of 0.001 to 50 μm and a porosity of 10 to 95 volume %, but is not limited thereto.

[0150] In an exemplary embodiment of the present invention, the separator may further include a porous coating layer on at least one surface of the porous substrate, and the porous coating layer may include inorganic particles and a binder.

[0151] In an exemplary embodiment of the present invention, the inorganic particles and the binder included in the porous coating layer may include inorganic particles and binders commonly used in the porous coating layer of the separator without limitation, and the preparation method thereof is not limited to a specific method.

[0152] Electrolyte

[0153] The electrolyte is a medium that moves ions participating in the electrochemical reaction of the lithium-sulfur battery, and contains a non-aqueous solvent and a lithium salt as an electrolyte.

[0154] The electrolytic solution is not limited to a specific composition, and may contain any composition used in a lithium secondary battery, specifically, a lithium-sulfur battery.

[0155] In an exemplary embodiment of the present invention, the electrolyte may include a non-aqueous solvent, a lithium salt, and an additive.

[0156] In an exemplary embodiment of the present invention, the nonaqueous solvent is not limited to a specific type and may include any nonaqueous solvent that can be used in a lithium-sulfur battery, such as ether solvents, esters, amides, linear carbonates, cyclic carbonates, and the like.

[0157] In an exemplary embodiment of the present invention, the ester may include, for example, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone or a mixture thereof, but is not limited thereto.

[0158] In an exemplary embodiment of the present invention, the linear carbonate may include, for example, any one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylmethyl carbonate, methylpropyl carbonate, and ethylpropyl carbonate, or a mixture thereof, but is not limited thereto.

[0159] In an exemplary embodiment of the present invention, the cyclic carbonate may include, for example, any one selected from the group consisting of ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate, and halides thereof. The halides may include, for example, fluoroethylene carbonate, etc., but are not limited thereto.

[0160] In an exemplary embodiment of the present invention, the non-aqueous solvent may include an ether solvent.

[0161] In an exemplary embodiment of the present invention, the content of the ether solvent may be 60% by volume or more, for example, 60% by volume to 100% by volume, 70% by volume to 100% by volume, 80% by volume to 100% by volume, 85% by volume to 100% by volume, 90% by volume to 100% by volume, 95% by volume to 100% by volume, 98% by volume to 100% by volume, 90% by volume to 98% by volume, or 90% by volume to 95% by volume, based on the total volume of the non-aqueous solvent. When the amount of the ether solvent is within the above range, it may have a favorable effect on the solubility of components of the electrolyte such as lithium salts, etc., but the present invention is not limited thereto.

[0162] In an exemplary embodiment of the present invention, the ether solvent may include an acyclic ether, a cyclic ether, or a mixture thereof.

[0163] In an exemplary embodiment of the present invention, the acyclic ether may include, for example, at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethylene ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether, and ethylene glycol ethyl methyl ether. Preferably, the acyclic ether may include at least one selected from the group consisting of dimethyl ether, dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether, more preferably dimethoxyethane.

[0164] In an exemplary embodiment of the present invention, the cyclic ether may include, for example, at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, 4,5-dimethyldioxolane, 4,5-diethyldioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dihydropyran, 1,4-dihydropyran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetra ... Preferably, the cyclic ether may include at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran and 2,5-dimethyltetrahydrofuran, more preferably 2-methylfuran.

[0165] In an exemplary embodiment of the present invention, the nonaqueous solvent may include a mixture of an acyclic ether and a cyclic ether.

[0166] In an exemplary embodiment of the present invention, the non-aqueous solvent may include dimethoxyethane (DME) and 2-methylfuran (2-MeF).

[0167] In an exemplary embodiment of the present invention, the volume ratio of the acyclic ether to the cyclic ether may be 5:95 to 95:5 (volume / volume), specifically 95:5 to 50:50, more specifically 90:10 to 70:30, 85:15 to 75:25 or 80:20 (volume / volume). In the present invention, the volume ratio is the ratio of "volume % of acyclic ether" to "volume % of cyclic ether" in the ether solvent.

[0168] In an exemplary embodiment of the present invention, in terms of the solubility of the electrolyte, the non-aqueous solvent may not include a carbonate solvent. Alternatively, the non-aqueous solvent may include a carbonate solvent in a small amount such that the carbonate solvent does not affect the solubility of the lithium salt. For example, when the non-aqueous solvent includes a carbonate solvent, based on the gross weight of the lithium secondary battery electrolyte, the content of the carbonate solvent may be 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.5% by weight or less, or 0% by weight (i.e., not included at all).

[0169] In an exemplary embodiment of the present invention, the lithium salt is not limited to a specific type and may include any lithium salt that can be used as a lithium secondary battery electrolyte. The lithium salt may include, for example, at least one of the following: LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborate, lower aliphatic lithium carbonate, lithium tetraphenylborate or lithium imide.

[0170] In an exemplary embodiment of the present invention, the concentration of the lithium salt may be appropriately determined according to ion conductivity, solubility, etc. For example, the concentration of the lithium salt may be 0.1 to 4 M, preferably 0.5 to 2 M. When the concentration of the lithium salt is within the above range, ion conductivity suitable for battery operation or optimal viscosity of the electrolyte may be ensured, thereby improving the mobility of lithium ions and suppressing the decomposition reaction of the lithium salt itself, but the present invention is not limited thereto.

[0171] In an exemplary embodiment of the present invention, the additive may include a nitrogen compound to improve the conductivity of the electrolyte and the life of the lithium-sulfur battery.

[0172] Specifically, the nitrogen compound can, for example, inhibit the reduction reaction of polysulfides during charge and discharge of lithium-sulfur batteries, thereby preventing the irreversible loss of polysulfides and improving the performance of lithium-sulfur batteries, but its effect is not limited thereto.

[0173] In an exemplary embodiment of the present invention, the nitrogen compound is not limited to a specific type, and may include any nitrogen compound that stably forms a solid electrolyte interface (SEI) of the negative electrode and improves charge / discharge efficiency. For example, the nitrogen compound may include a nitric acid compound, a nitrous acid compound, or a mixture thereof.

[0174] In an exemplary embodiment of the present invention, the nitrogen compound can be selected, for example, from: inorganic nitric acid or nitrous acid compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), ammonium nitrite (NH4NO2), etc.; organic nitric acid or nitrous acid compounds such as methyl nitrate, dialkyl imidazole nitrate , guanidine nitrate, imidazole nitrate , pyridine nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite, etc.; organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene, etc.; and combinations thereof, and may preferably contain lithium nitrate.

[0175] In an exemplary embodiment of the present invention, the content of the nitrogen compound may be, for example, 1 wt % to 10 wt %, 2 wt % to 10 wt %, or 3 wt % to 10 wt %, specifically 3 wt % to 8 wt %, 3 wt % to 6 wt %, or 3 wt % to 5 wt %, based on the total weight of the electrolyte, but is not limited thereto. When the amount of the nitrogen compound is within the above range, when used in a lithium-sulfur battery, the conductivity of the electrolyte may be improved and the reduction of polysulfides may be suppressed, but the present invention is not limited thereto.

[0176] In an exemplary embodiment of the present invention, in order to achieve high energy density, the lithium-sulfur battery may have an El / S weight ratio of 2.5 g / g or less, wherein the El / S weight ratio is a weight ratio of sulfur (S) in the electrolyte to the sulfur-carbon composite material of the positive electrode.

[0177] In an exemplary embodiment of the present invention, the El / S ratio of the lithium-sulfur battery may be 1.5 to 2.5 g / g, specifically 2 to 2.5 g / g, 2 to 2.3 g / g, 2.0 to 2.2 g / g, or 2.0 to 2.15 g / g.

[0178] In an exemplary embodiment of the present invention, the El / S ratio of the lithium-sulfur battery can be calculated by the ratio of the weight of the electrolyte to the weight of the sulfur in the sulfur-carbon composite material of the positive electrode used in the manufacturing step immediately after manufacturing the lithium-sulfur battery.

[0179] In another exemplary embodiment of the present invention, the El / S ratio of the lithium-sulfur battery can be calculated by the ratio of the weight of the electrolyte to the weight of the sulfur in the sulfur-carbon composite material of the positive electrode analyzed by disassembling the battery.

[0180] For example, when the El / S ratio of a lithium-sulfur battery is analyzed by disassembling the battery, after measuring the total weight of the lithium-sulfur battery in a charged state, the lithium-sulfur battery can be disassembled, the positive electrode, the negative electrode, the separator and the shell can be washed and dried, the sum of the weights of the components can be obtained, and the weight of the electrolyte can be measured by subtracting the weight of the positive electrode, the negative electrode, the separator and the shell from the measured total weight of the battery. In this case, the solvent used for washing may preferably be a solvent for extracting the electrolyte contaminated on the positive electrode, the negative electrode, the separator and the shell. Subsequently, the weight of sulfur in the positive electrode can be measured by separating the positive electrode active material layer and the current collector from the dried positive electrode, and measuring the weight of sulfur obtained from the sulfur-carbon composite material present in the positive electrode active material layer. The El / S ratio of the lithium-sulfur battery can be calculated by the ratio of the weight of the electrolyte to the weight of sulfur in the sulfur-carbon composite material of the positive electrode.

[0181] In an exemplary embodiment of the present invention, the weight of sulfur obtained from the sulfur-carbon composite material present in the positive electrode active material layer can be measured, for example, by performing TGA analysis on a resultant obtained by stripping the obtained positive electrode active material layer to measure the amount of sulfur (S) obtained from the active material, but the measurement method is not limited thereto.

[0182] In an exemplary embodiment of the present invention, the state of charge when the lithium-sulfur battery is disassembled may be a fully charged state, ie, SOC 100%.

[0183] In another exemplary embodiment of the present invention, the lithium-sulfur battery may be disassembled at SOC 95% to SOS 100%.

[0184] In an exemplary embodiment of the present invention, when disassembling a lithium-sulfur battery in a charged state, an inert atmosphere is preferred in terms of safety. For example, the lithium-sulfur battery can be disassembled under an Ar atmosphere.

[0185] In an exemplary embodiment of the present invention, the lithium-sulfur battery may exhibit an energy density of, for example, 400 Wh / kg or more. Specifically, the energy density of the lithium-sulfur battery may be 420 Wh / kg or more, more specifically 430 Wh / kg or more. For example, the energy density of the lithium-sulfur battery may be 400 Wh / kg to 1,000 Wh / kg, specifically 410 Wh / kg to 800 Wh / kg, 420 Wh / kg to 600 Wh / kg, specifically 430 Wh / kg to 550 Wh / kg.

[0186] In an exemplary embodiment of the present invention, the energy density of the lithium-sulfur battery can be measured by any known method without limitation. For example, the energy density of the lithium-sulfur battery can be calculated according to the following formula based on the specific capacity measured after discharging and charging one or more times in the range of 1.8 V to 2.7 V at room temperature and then discharging at 0.1 C.

[0187] In an exemplary embodiment of the present invention, the initial discharge and the initial charge may each be performed at 0.1 C to 0.3 C. Specifically, the initial discharge and the initial charge may each be performed at 0.1 C to 0.2 C, for example, 0.1 C.

[0188] Furthermore, in an exemplary embodiment of the present invention, initial discharge and initial charge may each be repeatedly performed three times at 0.1C.

[0189] In the following formula, the discharge capacity, driving voltage and battery weight can be measured in mAh, V and kg respectively.

[0190] [formula]

[0191] Energy density (Wh / kg) = [(discharge capacity (mAh) × driving voltage (V))] / (battery weight (kg))

[0192] In an exemplary embodiment of the present invention, the room temperature may be, for example, 23°C to 25°C, specifically 23°C.

[0193] In an exemplary embodiment of the present invention, the charge / discharge rate may be 0.1 to 0.5 C rate, for example, 0.3 C rate. The charge / discharge rate is not limited to a specific range, and may include the above C rate range.

[0194] In an exemplary embodiment of the present invention, the lithium-sulfur battery may have various shapes such as a pouch type or a cylindrical shape, but is not limited thereto.

[0195] According to another aspect of the present invention, a method for evaluating the energy density of a lithium-sulfur battery by a diffraction angle in an XRD pattern of the lithium-sulfur battery is provided.

[0196] In an exemplary embodiment of the present invention, the lithium-sulfur battery to be evaluated may include: a positive electrode including a sulfur-carbon composite material, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte. In addition, the lithium-sulfur battery may include a shell containing an electrode assembly including a positive electrode, a negative electrode and a separator, and an electrolyte.

[0197] The evaluation method includes the step of determining a lithium-sulfur battery containing a compound as a battery with high energy density, wherein the compound has three or more characteristic peaks in a diffraction angle (2θ value) of an XRD pattern selected from the following at DOD 15% to DOD 80%: 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2° and 15.0±0.2°.

[0198] In an exemplary embodiment of the present invention, an XRD pattern may be obtained from real-time charge / discharge XRD measurement results of a lithium-sulfur battery.

[0199] Specifically, in an exemplary embodiment of the present invention, the evaluation method may include evaluating by obtaining XRD results in real time while charging the lithium-sulfur battery to SOC 100% at 0.1 C to 0.3 C, such as 0.2 C, and then discharging at 0.05 C to 0.2 C, such as 0.1 C.

[0200] In an exemplary embodiment of the present invention, DOD 15% to DOD 80% may be a state having a potential of 1.7 V to 2.2 V.

[0201] In addition, in an exemplary embodiment of the present invention, DOD 15% to DOD 80% may be a material having a capacity of 150 to 960 mAh / g ( S )'s state of discharge capacity per unit sulfur weight.

[0202] In an exemplary embodiment of the present invention, the battery having a high energy density may be, for example, a battery having an energy density of 300 Wh / kg or more, specifically 430 Wh / kg or more. For example, the lithium-sulfur battery may be a battery having an energy density of 400 Wh / kg to 1,000 Wh / kg, specifically 410 Wh / kg to 800 Wh / kg, 420 Wh / kg to 600 Wh / kg, specifically 430 Wh / kg to 550 Wh / kg.

[0203] Hereinafter, examples are given to help understand the present invention. However, the following examples are provided as illustrations, and it is apparent to those skilled in the art that various changes and variations can be accomplished within the scope of the present invention and technical aspects, and these changes and variations are within the scope of the appended claims.

[0204] [Preparation of lithium-sulfur batteries]

[0205] Example 1

[0206] A sulfur-carbon composite material prepared by mixing inorganic sulfur (S8) and carbon nanotubes (CNT) (S / C weight ratio = 2.33) was used as a positive electrode active material. A positive electrode slurry composition was prepared by mixing 96 wt % of the prepared sulfur-carbon composite material with 4 wt % of PAA (polyacrylate) as a binder. The positive electrode slurry composition was coated on an aluminum current collector and dried to prepare a positive electrode. The sulfur (S) loading of the positive electrode was 3.7 mAh / cm 2 .

[0207] A 60 μm thick metallic lithium was used as the negative electrode.

[0208] The electrode assembly was prepared by placing the positive electrode and the negative electrode facing each other with a polyethylene separator having a thickness of 12 μm and a porosity of 46 volume % interposed therebetween.

[0209] After the prepared electrode assembly was packed in a pouch-type case, a lithium-sulfur battery was prepared by injecting an electrolyte with an El / S ratio of 2.15 g / g, in which 0.75 M of lithium salt (LiTFSI) and 3 wt % of lithium nitrate (LiNO3) were dissolved in an 8:2 (vol / vol) mixed solvent of dimethoxyethane (DME) and 2-methylfuran (2-MeF).

[0210] Comparative Example 1

[0211] In addition to the sulfur (S) loading of the positive electrode of 2.7 mAh / cm 2 A lithium-sulfur battery was prepared in the same manner as in Example 1, except that the El / S ratio was 2.9 g / g.

[0212] Comparative Example 2

[0213] In addition to the sulfur (S) loading of the positive electrode of 3.5 mAh / cm 2 A lithium-sulfur battery was prepared in the same manner as in Example 1, except that the El / S ratio was 2.60 g / g.

[0214] Comparative Example 3

[0215] In addition to the sulfur (S) loading of the positive electrode of 3.5 mAh / cm 2 A lithium-sulfur battery was prepared in the same manner as in Example 1, except that the El / S ratio was 3.00 g / g.

[0216] [Evaluation of battery performance]

[0217] The lithium-sulfur batteries prepared in Example 1 and Comparative Examples 1 to 3 were repeatedly discharged and charged three times at room temperature (23°C) at a rate of 0.1C in the range of 1.8 V to 2.7 V, and then the specific capacity of the battery was measured under 0.1C discharge conditions, and the energy density (Wh / kg) of the battery was evaluated.

[0218] For each of the batteries prepared in Example 1 and Comparative Examples 1 to 3, values ​​according to the following Formula 1 were calculated, and Table 1 summarizes the values.

[0219] [Formula 1]

[0220] S X =S PE / S EL / S

[0221] Among them, S PE represents the sulfur (S) loading in the cathode, and

[0222] S EL / S It represents the weight ratio of electrolyte to elemental sulfur (S) in the sulfur-carbon composite material (E1 / S weight ratio).

[0223] Figure 1 Shown are the results of evaluating the capacities of the batteries of Example 1, Comparative Example 2, and Comparative Example 3. The energy densities of the batteries of Example 1 and Comparative Examples 1 to 3 were calculated according to the following formula, and Table 1 summarizes the energy densities.

[0224] [formula]

[0225] Energy density (Wh / kg) = {[(discharge capacity (mAh) × driving voltage (V)) / 1000] / (battery weight (kg))}

[0226]

[0227] [Evaluation of XRD pattern of battery]

[0228] Real-time charge / discharge XRD patterns of the lithium-sulfur batteries prepared in Example 1 and Comparative Examples 1 to 3 were obtained by the following Operato XRD analysis.

[0229] First, for each battery of Example 1 and Comparative Example 1, a real-time charge / discharge XRD pattern was obtained while activating by discharging to 1.8 V at 0.1 C at room temperature (23° C.), charging to 2.7 V at 0.2 C, and then discharging from 2.7 V to 1.8 V at a 0.1 C rate.

[0230] In addition, for each battery of Comparative Examples 2 and 3, a real-time charge / discharge XRD pattern was obtained while activating by discharging to 1.8 V at 0.1 C at room temperature (23° C.), charging to 2.7 V at 0.1 C, and then discharging from 2.7 V to 1.8 V at a 0.1 C rate.

[0231] Specifically, the Mo Kα X-ray (λ=0.709 ) 2 theta (2θ) ranging from 7° to 17° was measured in transmission mode. Each pattern was acquired at 0.014° intervals for a total of 3 minutes. XRD measurements were performed using a press fixture equipped with a Be window.

[0232] The obtained real-time charge / discharge XRD measurement results are shown in Figure 2a (Example 1), Figure 3a (Comparative Example 1), Figure 4a (Comparative Example 2) and Figure 5a (Comparative Example 3). Figure 2a , Figure 3a , Figure 4a and Figure 5a The measurement results from SOC 0% to SOC 100% and from DOD 0% to DOD 100% are shown starting from the left side of the image.

[0233] In this case, refer to Figure 2a , Figure 3a , Figure 4a , Figure 5a According to the results of Table 1, in the discharge state, Example 1 shows a characteristic peak that is not detected in Comparative Examples 1 to 3. Specifically, in the range between DOD 15% (index of about 130) and DOD 80% (index of about 230), Example 1 shows a characteristic peak that is not detected in Comparative Examples 1 to 3.

[0234] Specifically, in order to confirm the characteristic peaks observed only in Example 1 ( Figure 2a ), the XRD patterns of DOD 22% were obtained from the real-time charge / discharge XRD measurement results of the batteries of Comparative Examples 1 to 3. Figure 2b (Example 1), Figure 3b (Comparative Example 1), Figure 4b (Comparative Example 2) and Figure 5b (Comparative Example 3) shows the XRD pattern.

[0235] Reference Figure 3b to Figure 5b The diffraction angles of the characteristic peaks observed only in Example 1 under the discharge state, typically at DOD 22%, are as follows.

[0236] Example 1 (2θ value): 7.1°, 9.0°, 9.4°, 9.6°, 9.9°, 10.0°, 10.4°, 11.0°, 11.6°, 12.1°, 13.3°, 14.5°, 15.0°.

[0237] Reference Figure 3b (Comparative Example 1), Figure 4b (Comparative Example 2) and Figure 5b (Comparative Example 3), less than three characteristic peaks were observed in the region where the characteristic peaks of Example 1 were observed.

[0238] According to the comparison of discharge distribution between Example 1, Comparative Example 2 and Comparative Example 3 Figure 1 , no significant difference in discharge capacity was seen between them, but the XRD patterns in FIGS. 2 to 5 show that a specific crystallized reactant was detected only in Example 1. In this case, when the energy density between the batteries is compared through Table 1, the discharge capacity of Example 1 is 440 Wh / kg, and the discharge capacities of Comparative Example 2 and Comparative Example 3 are 420 Wh / kg and 400 Wh / kg, respectively, and it is found that, although the levels of discharge capacity are similar, there is a difference in energy density.

[0239] That is, it was confirmed that, like the formula for calculating the energy density, since the energy density takes both the battery weight and the driving voltage into consideration, it is inappropriate to estimate the energy density only from the discharge capacity.

[0240] In addition, in order to realize a lithium-sulfur battery with high energy density, it is necessary to maintain high reactivity despite the solid phase reaction in the battery. X The value is 1.4 mAh / cm 2 In the above Example 1, characteristic peaks in XRD were detected, and it is presumed that the battery according to Example 1 exhibits high energy density due to high reactivity despite the presence of a solid phase reaction in the battery.

[0241] Although the present invention has been described above using a limited number of embodiments and drawings, the present invention is not limited thereto and those skilled in the art may make various changes and modifications thereto within the technical aspects of the present invention and the scope of the appended claims and their equivalents.

Claims

1. A lithium-sulfur battery, comprising: A positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte comprising a sulfur-carbon composite material. in, The lithium-sulfur battery comprises a compound having three or more characteristic peaks selected from the group consisting of diffraction angles (2θ values) of an X-ray diffraction (XRD) pattern at a depth of discharge (DOD) of 15% to DOD 80%: 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2°, and 15.0±0.2°.

2. The lithium-sulfur battery according to claim 1, wherein The DOD 15% to DOD 80% is a state having a potential of 1.7 V to 2.2 V.

3. The lithium-sulfur battery according to claim 1, wherein The DOD 15% to DOD 80% is a state having a discharge capacity per sulfur (S) weight of 150 mAh / g(s) to 960 mAh / g(s).

4. The lithium-sulfur battery according to claim 1, wherein The compound has four or more characteristic peaks selected from the diffraction angles.

5. The lithium-sulfur battery according to claim 1, wherein: The compound comprises diffraction angles (2θ values) of the XRD pattern of 7.1±0.2°, 9.0±0.2°, 9.4±0.2°, 9.6±0.2°, 9.9±0.2°, 10.0±0.2°, 10.4±0.2°, 11.0±0.2°, 11.6±0.2°, 12.1±0.2°, 13.3±0.2°, 14.5±0.2°, and 15.0±0.2°.

6. The lithium-sulfur battery according to claim 1, wherein: The sulfur-carbon composite material has a sulfur / carbon (S / C) weight ratio of 2.3 g / g or more.

7. The lithium-sulfur battery according to claim 1, wherein: The positive electrode comprises: Current collector; and a positive electrode active material layer comprising the sulfur-carbon composite material on at least one surface of the current collector, and The weight of the sulfur-carbon composite material is greater than or equal to 90 wt % based on the total weight of the positive electrode active material layer.

8. The lithium-sulfur battery according to claim 1, wherein: The positive electrode has 2 mAh / cm 2 Up to 5 mAh / cm 2 of sulfur (S) loading.

9. The lithium-sulfur battery according to claim 1, wherein: The negative electrode has a thickness of 40 μm to 80 μm.

10. The lithium-sulfur battery according to claim 1, wherein: The weight ratio of the electrolyte to the elemental sulfur (S) in the sulfur-carbon composite material (E1 / S weight ratio) is less than 2.5 g / g.

11. The lithium-sulfur battery according to claim 1, wherein: The lithium-sulfur battery has a capacity of 1.4 mAh / cm 2 Above S X , S X Satisfies the following formula 1: [Formula 1] S X =S PE / S EL / S Among them, S PE is the sulfur (S) loading in the cathode, and Among them, S EL / S is the weight ratio of the electrolyte to the elemental sulfur (S) in the sulfur-carbon composite material (E1 / S weight ratio).

12. The lithium-sulfur battery according to claim 1, wherein: The energy density of the lithium-sulfur battery is above 430 Wh / kg.

13. The lithium-sulfur battery according to claim 1, wherein: The lithium-sulfur battery is a pouch-type battery or a cylindrical battery.

14. A method for evaluating the energy density of a lithium-sulfur battery, the lithium-sulfur battery comprising: a positive electrode comprising a sulfur-carbon composite material, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, the method comprising: A lithium-sulfur battery containing a compound having three or more characteristic peaks selected from the following diffraction angles (2θ values) of an X-ray diffraction (XRD) pattern at a depth of discharge (DOD) of 15% to DOD 80% is determined to be a battery with a high energy density.

15. The evaluation method according to claim 14, wherein: The battery having a high energy density is a battery having an energy density of 430 Wh / kg or more.

Citation Information

Patent Citations

  • Systems and methods for supporting synchronization

    KR1020230074500A

  • Door handle device for vehicle door

    KR1020230155551A